Arabic Language Learning Based On Erikson's Developmental Psychology Theory/ Pembelajaran Bahasa Arab Berbasis Teori Psikologi Perkembangan Erikson - Diniyah, Nashfah Maslahatul; Kholis, Nur (Bumi Lingua Edu Center, 2024)
Skinner's behaviorist theory is a behavior change caused by the interaction between stimulus and response. This theory views learning as a change in student behavior. The purpose of this study is to describe B.F. Skinner's behaviorist theory, its implementation in Arabic speaking skill/ maharah kalam learning, and the problems in its application. The research method used is a literature study with a qualitative approach. Research results 1. Behaviorist learning theory is a behavior change caused by the interaction between stimulus and response. This theory views learning as a change in student behavior. 2. The implementation of behaviorism for kalam learning includes the introduction of maharah, the creation of a conducive environment, using supportive learning media, and providing reinforcement as a positive response to student behavior. Applying Skinner's behaviorist theory has proven effective in Maharah Kalam's learning, especially in creating a supportive learning environment and providing positive reinforcement. 3. The problems in its application include internal factors, such as intelligence, which influences their ability to adapt to the environment when learning Arabic, especially in learning to communicate in that language.